HUBUNGAN KEPATUHAN KONSUMSI TTD DENGAN KADAR HEMOGLOBIN PADA REMAJA PUTERI WILAYAH PUSKESMAS BENGKURING TAHUN 2019 - Dwi Pramardika, Dhito; Fitriana (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2019)
The total consumption of blood added tablets as much as â‰¥ 52 tablets carried out for teenage girls in Indonesia is only 1.4% and the prevalence of anemia in teenage girls is currently at 48.9% (Riskesdas, 2018). Based on this, this study aims to determine and analyze the relationship of compliance with blood added tablets consumption with hemoglobin (Hb) levels. This research is descriptive research. The one used in this study is a type of correlation research. The sample size in this study is as many as 45 respondents using purposive sampling. The data in this study were processed using Rank Spearman correlation test. There is a significant relationship between the variables of compliance consumption of BAT with Hb levels with a p value of 0.019. With a coefficient value of 0.349 which means moderate and unidirectional, namely increasing compliance consumption of BAT,it will also increase blood hemoglobin (Hb) levels. There is arelationship between Compliance consumption of Iron Suplement (TTD and hemoglobin levels (Hb).